Spirochetal Lipoproteins and Immune Evasion - Christodoulides, Alexei; Boyadjian, Ani; Kelesidis, Theodoros (Frontiers in Immunology, 2017)
Spirochetes are a major threat to public health. However, the exact pathogenesis of spirochetal diseases remains unclear. Spirochetes express lipoproteins that often determine the cross talk between the host and spirochetes. Lipoproteins are pro-inflammatory, immunomodulatory and enable the spirochetes to evade the immune system. Herein, the immunomodulatory effects of spirochetal lipoproteins related to immune evasion are reviewed. Understanding lipoprotein-induced immunomodulation will aid in elucidating innate pathogenesis processes and subsequent adaptive mechanisms potentially relevant to spirochetal disease vaccine development and treatment.